Automation of Trolley Wire Adjustment to Improve Safety of Deviation Maintenance on Japanese Type Catenary Networks - Yang, Guang; Chiau, Li; Jiadong, Whu (Nusantara Publisher, 2024)
The deviation Maintenance is an examination activity including measurement of the trolley wire deviation angle, the height of the trolley wire to the rail, and adjust the deviation of trolley wire on the catenary system or Overhead Contact Systems (OCS). All maintenance activities are carried out along railway lines and handled directly by workers. Implementation of this deviation maintenance is very rich and full of risks, because all work is still done manually by the workers. In this research we will create a prototype of automatic trolley wire measurement and adjustment equipment using Arduino uno microcontroller and some supporting sensors such as ultrasonic sensor and laser receiver sensor. For drives using a dc motor actuator that serves to pull or push the trolley wire to form an appropriate angle deviation.